Kontaminált őstörök igei bázisok - Berta Árpád (2001)
The article explores the possibilities of contamination among Ancient Turkic verb bases. The author selects three Ancient Turkic verbs from the available corpus (ywl(X')- 'to pull out, pluck out', ywl(X)~ 'to redeem', ytili- 'to shave') in order to illustrate through them the multiplicity of problems emerging from this phenomenon, one which has not been addressed sufficiently in Turkic linguistics. At the end of the article, the author also recommends a Turkic etymology for the Hungarian word gyilkos 'murderer' which has until now been considered of unknown origin in the literature on Hungarian word origins.
Keywords: Bölcsészettudományok; Nyelvek és irodalom